Bibliometric Analysis of Digital Entrepreneurship - Octavia, Devi; Noor Zahara, Cyntia; Setiawan, Adi; Agustina, Agustina (Malikussaleh University, Aceh, Indonesia, 2025)
This research explores the dynamics of entrepreneurship in the digital era by analyzing research trends, the impact of technological innovation, and the challenges and opportunities entrepreneurs face in the face of global market changes. Using a qualitative approach with bibliometric methods, this research identifies the development of the concept of entrepreneurship from 1956 to 2025. The research expanded significantly starting in 2016, along with the increasing adoption of digital technology in various industrial sectors. Visualization of bibliometric data shows that global entrepreneurship is a significant topic in academic literature. It is interconnected with digital business, corporate entrepreneurship, and entrepreneurial process. The findings of this study show that entrepreneurship is increasingly integrated with the digital world, with social media and digital technology acting as significant factors in accelerating business growth. The results of this analysis are expected to serve as a reference for further research in the evolving field of entrepreneurship and provide insights for business practitioners and policymakers in designing innovative strategies in the digital era.